Veiling and lipstick in the city being female, young and Muslim in urban Mindanao - Taqueban, Efenita M. (2018)
Access online through this link: https://saliksik.upd.edu.ph/storage/submission/pdf/manuscripts/qCOnjuxpVDKatKdKP5fjUpVUSE6fJ2tauAA47P9b.pdf
Keywords: Muslim women; Young women; Cosmetics; Mindanao